In vitro glycemic index, antioxidant capacity, and sensorial properties of breads enriched with broccoli sprouts - Bayram, Hatice Merve; Ozkan, Kubra; Yildirim, Guldane; Yilmaz, Melike Yagmur; Ozturkcan, Arda; Sagdic, Osman (EMERALD GROUP PUBLISHING LTD, 2025)
Purpose - This study aims to investigate the glycemic index (GI), total phenolic content, total flavonoid content, antioxidant capacity and sensory properties of the breads enriched with fresh and freeze-dried (FD)-broccoli sprouts (BS). Design/methodology/approach - Broccoli was sprouted using a home germination system. The bread was made with organic wheat flour consisting of fresh and FD-BS. The moisture content of the breads was measured using a moisture meter. The texture properties of raisins were measured by a texture analyzer. Total phenolic contents (TPC), total flavonoid contents (TFC) and antioxidants assays (DPPH, ABTS, FRAP) and the in vitro GI of breads were determined. Additionally, the hedonic test was used to determine the degree of overall liking for the breads based on the degree of liking or disliking according to a five-point hedonic scale. Findings - Enriching organic bread with fresh and FD-BS significantly increased the total phenolic, flavonoid contents and antioxidant capacities, with the most pronounced effects observed in breads enriched with FD-BS (p< 0.05). The GI values of breads vary between 69.8 and 73.4. Increased green color, crust and crumb color intensity were observed in BS-enriched breads (p< 0.05). The general acceptance of breads was not affected by addition of BS. Originality/value - This study addresses the effects of FD-BS incorporation into organic wheat flour bread demonstrating that they reduce the in vitro GI and increase the TPC, TFC and antioxidant power. The findings could open up new opportunities for food processors and sustainable nutrition.
Keywords: Sustainability; Germination; Broccoli; Freeze-drying; Glycemic index; Bread; QUALITY; LIGHT; Food Science & Technology